THE EFFECT OF SERVICE QUALITY TOWARDS GO-RIDE CUSTOMER SATISFACTION IN MALANG CITY - Fani Firmansyah; Ike Nurjanah (Journal of Management and Business, 2020)
Malang is a densely populated city with 927,285 residents. This has an impact on the development of transportation to meet daily needs. Transportation services are very diverse, such as public transportation, buses, and motorcycle taxis. Nowadays, motorcycle taxi services have developed into online motorcycle taxis that provide convenience to the public. One of the services is Go-Ride. This transportation service is often used by customers in the city of Malang. Therefore, it becomes important to know the level of customer satisfaction fluctuates with the various services provided. The research is conducted by using quantitative method with random sampling technique (accidental sampling) of 100 respondents from 5 districts. The sampling technique use multiple linear regression analysis that is the analysis used with test instruments (validity and reliability tests) and classical assumption tests (tests of normality, heteroscedasticity and multicollinearity) as analytical tools. The results of this study are evidence of physical approval/ tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) on customer satisfaction (Y) simultaneously having an influence significant. However, physically only tangible / physical evidence (X1) and empathy (X5) to related customer satisfaction, while other variables are not related such as Reliability (X2), Responsiveness (X3) and Assurance (X4).